Oncogenic Roles and Inhibitors of DNMT1, DNMT3A, and DNMT3B in Acute Myeloid Leukaemia. Issue 14 (May 2019) - Wong, Kah Keng; Lawrie, Charles H; Green, Tina M
Epigenetic alteration has been proposed to give rise to numerous classic hallmarks of cancer. Impaired DNA methylation plays a central role in the onset and progression of several types of malignancies, and DNA methylation is mediated by DNA methyltransferases (DNMTs) consisting of DNMT1, DNMT3A, and DNMT3B. DNMTs are frequently implicated in the pathogenesis and aggressiveness of acute myeloid leukaemia (AML) patients. In this review, we describe and discuss the oncogenic roles of DNMT1, DNMT3A, and DNMT3B in AML. The clinical response predictive roles of DNMTs in clinical trials utilising hypomethylating agents (azacitidine and decitabine) in AML patients are presented. Novel hypomethylating agent (guadecitabine) and experimental DNMT inhibitors in AML are also discussed. In summary, hypermethylation of tumour suppressors mediated by DNMT1 or DNMT3B contributes to the progression and severity of AML (except MLL-AF9 and inv(16)(p13;q22) AML for DNMT3B), while mutation affecting DNMT3A represents an early genetic lesion in the pathogenesis of AML. In clinical trials of AML patients, expression of DNMTs is downregulated by hypomethylating agents while the clinical response predictive roles of DNMT biomarkers remain unresolved. Finally, nucleoside hypomethylating agents have continued to show enhanced responses in clinical trials of AML patients, and novel non-nucleoside DNMT inhibitors have demonstrated cytotoxicity against AML cells in pre-clinical settings.